If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -7) + -3(x + -4) = 1 Reorder the terms: 2(-7 + x) + -3(x + -4) = 1 (-7 * 2 + x * 2) + -3(x + -4) = 1 (-14 + 2x) + -3(x + -4) = 1 Reorder the terms: -14 + 2x + -3(-4 + x) = 1 -14 + 2x + (-4 * -3 + x * -3) = 1 -14 + 2x + (12 + -3x) = 1 Reorder the terms: -14 + 12 + 2x + -3x = 1 Combine like terms: -14 + 12 = -2 -2 + 2x + -3x = 1 Combine like terms: 2x + -3x = -1x -2 + -1x = 1 Solving -2 + -1x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 1 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 1 + 2 -1x = 1 + 2 Combine like terms: 1 + 2 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3
| y+165+(8y-75)=180 | | 5+4(x-3)-3x=-11 | | V=(56)(68)(53) | | 5x+4x-39=26-4x | | -22=6+4x-9(x+2) | | 7x^2+62x=135 | | -74=8z | | 3x-10+4x-1=3 | | 8x+9x-100=50-8x | | -2y+1-9y+1+-22y+11+2=180 | | -6x+5(2x+4)=-8 | | 4xsqaured-3x+3=0 | | -7x+8+8x=7+x+1 | | 4*x^3+6*x=0 | | 2(x+5)=-3x+5(x+2) | | sqrt(6x-4)-1=sqrt(3x+1) | | 2n+36=-104 | | 4x+166=9x+236 | | 9a+5=77 | | y=2x^2+16x+24 | | -30=6p | | 28+25m=42+18 | | 5x+141=8x+171 | | 8(2l+6)=128 | | =6p | | 4x+5=5x-35 | | 5x-2+6y+7=180 | | 8(2l*6)=128 | | -0.5+0.25x=15-x | | 1x-9=9 | | 10+2(x-7)=-12 | | 4n-11=23+2n |